Research on key technologies of multi-element monitoring data integration in intelligent mine - LI Guomin; ZHANG Ao; HE Yaoyi; GAO Wen; HUANG Zongliu (Gong-kuang zidonghua, 2022)
Currently, most coal mine monitoring systems adopt private data acquisition protocols, which are incompatible with each other. In order to solve this problem, the key technologies of multi-element monitoring data integration in intelligent mine are discussed from three aspects of data acquisition, data fusion and data storage. Data acquisition: In order to strengthen the openness and compatibility of the system, the private protocol can be encapsulated into a driver dynamic link library (DLL). The data acquisition of each business system can be realized by loading and adapting OPC, MQTT and other protocols and hooking the private protocol driver. The multithreading technology can be adopted to meet the requirements of high efficiency and real-time of multi-channel and multi-protocol data transmission. Data fusion: The data with the high frequency of sharing among various systems can be unified and standardized to form the master data of the coal mine. This will ensure the consistency of data among various systems. Data storage: For data with high real-time requirements, the time series database can be selected. For data with low real-time requirements, the relational database can be selected. Through comparative analysis, InfluxDB is more suitable for real-time storage of coal mine monitoring data, and MySQL Community is more suitable for data storage with low real-time requirements. Redis cache technology can be used to achieve efficient data cache so as to ensure the integrity of coal mine monitoring data.